Taxonomic and biogeographical analysis of diatom assemblages from historic bryophyte samples from Campbell Island (sub-Antarctic) - Goeyers, Charlotte; Vitt, Dale H.; Van de Vijver, Bart (Plant ecology and evolution, 2022)
Background and aims – The past two decades, the non-marine diatom flora in the sub-Aantarctic region has been intensively revised. Historic collections provide excellent tools for answering taxonomic, community-related, and biogeographical questions. This study analysed the moss-inhabiting diatom flora from sub-Antarctic Campbell Island in samples collected in 1969–1970 and retrieved from the British Antarctic Survey herbarium (Cambridge, UK). With this study we attempt to expand our, till now sparse, knowledge on the moss-inhabiting diatom flora in the southern Pacific Ocean. Material and methods – In total, the diatom composition in 32 moss samples has been analysed using Light Microscopy (LM) and Scanning Electron Microscopy (SEM). A biogeographical analysis and community analysis of the Campbell Island diatom flora were conducted. Key results – Analysis of the Campbell Island diatom flora revealed the presence of 141 taxa belonging to 45 genera. The species composition in the dominant genera Planothidium , Humidophila , and Psammothidium , the presence of Epithemia , Rhopalodia , Cocconeis , uncommon in the sub-Antarctic region, and many unidentified taxa point to the uniqueness of the Campbell Island diatom flora. The biogeographical analysis showed an overall low similarity with the other sub-Antarctic and the Maritime Antarctic islands. Four different diatom assemblages were distinguished following the community analysis. Moisture level and habitat type seem to be the main factors shaping the Campbell Island diatom assemblages. Conclusion – The results of the Campbell Island diatom analysis highlight the importance of historic herbarium material. Since the examined flora is largely composed of unknown (presumably new) species, it is vital to analyse additional (historic) samples to complete the assessment of the moss diatom assemblages from Campbell Island.